PULMONARY MANIFESTATIONS IN PATIENTS WITH ACHALASIA: The connection between lungs and achalasia - Jankovic, Jelena; Skrobic, Ognjan; Milenkovic, Branislava (Medicinski podmladak, 2023)
Achalasia is motility disorder caused by insufficient lower esophageal sphincter relaxation. Patient with achalasia, addition to gastrointestinal symptoms, also have many respiratory symptoms. The mechanisms of lung involvement in those patients may include an extrinsic compression of the trachea from dilated esophagus or aspiration of undigested food. Aim of this study to evaluate clinical, structural and functional lung abnormalities in patients with achalasia. Respiratory symptoms can be caused aspirated sour undigested contents that irritate the respiratory mucosa and retention of food in the lower esophagus can cause chest pain. The most commonly symptoms are cough, dyspnea, retrosternal pain, dysphonia. Recurrent micro or macro-aspirations can cause structural changes of the airways and lung parenchyma such as fibrosis, nodular changes and even pneumonia as acute pulmonary manifestation. Compression on bronchial tree can cause obstructive finding on spirometry tests but also restrictive finding can be associated with fibrosis. Decreased diffusion capacity of the lungs is  probably consequence of damage alveolar-capillary membrane with acidic gastric undigested contents. Respiratory symptoms, radiological and functional abnormalities are common in patients with achalasia. Awareness of this association is important in early diagnostic and treatment.
Keywords: achalasia; functional pulmonary tests; respiratory symptoms; chest CT scan